PENGGUNAAN MEDIA ANIMASI UNTUK MENINGKATKAN KEMAMPUAN LITERASI LINGKUNGAN PESERTA DIDIK SMP NEGERI 4 WARU - Febriliani, Avelin; Budiyanto, Mohammad (Universitas Negeri Surabaya, 2025)
Environmental literacy in Indonesia, cumulatively, still needs improvement. Efforts to enhance literacy can be made using engaging and educational media, such as animation. This research aims to describe the improvement of students' environmental literacy after the use of animated media. This type of research is pre-experimental with a one-group pretest-posttest design. Data collection techniques used environmental literacy instruments and student responses. Data analysis techniques employed n-gain analysis and paired t-tests. The research findings are: (1) there was an increase in students' environmental literacy as evidenced by a low-criterion gain score; (2) there was a significant difference between the pretest and posttest results. Based on the research, it is concluded that the use of animation is capable of improving environmental literacy. This research has implications for students and teachers. Students develop curiosity about the material to be delivered by the teacher. Teachers can also creatively incorporate animation into the material or other learning stages. Based on the research findings, suggestions are offered to teachers to utilize animation as a learning medium, to future researchers to increase the intensity of learning to obtain more robust data, and to students to be aware of the importance of protecting the environment.